Mortality in Critically Ill Elderly Individuals Receiving Mechanical Ventilation - Santa Cruz, Roberto; Villarejo, Fernando; Figueroa, Alvaro; Cortes-Jofre, Marcela; Gagliardi, Juan; Navarrete Signorile, Marcelo Alejandro (My University, 2019)
BACKGROUND: Previous studies that evaluated mortality in elderly subjects who received mechanical ventilation had conflicting results. The aim of this systematic review was to evaluate the effects of age on mortality. METHODS: A number of medical literature databases and the references listed (from 1974 to May 2015) were searched for studies that compared 2 different age groups. The primary outcome was mortality in subjects ages > 65 y. The severity scores, ICU and hospital lengths of stay, and the presence of ventilator-associated pneumonia were secondary outcomes. Finally, mortality in the subjects with ARDS and of cutoff ages 70 and 80 y was assessed by subgroup analysis. Evidence quality was assessed by the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) criteria score. RESULTS: Of the 5,182 articles identified, 21 were included. Subjects ages >= 65 y had higher mortalities (odds ratio [OR] 1.80, 95% CI 1.56 -2.08; I-2 = 71%). APACHE (Acute Physiology and Chronic Health Evaluation) II revealed intergroup differences (mean difference 3.07, 95% CI 2.52-3.61; I-2 = 0%), whereas neither the ICU nor hospital length of stay (mean difference 1.27, 95% CI = 0.82 to 3.36, I-2 = 82%, and mean difference 1.29, 95% CI = 0.71 to 3.29, I-2 = 0%, respectively) nor the groups in the 2 studies that assessed ventilator-associated pneumonia exhibited any difference. Subgroup analysis revealed a higher mortality in the older subjects, in the subjects with ARDS (OR 1.76, 95% CI 1.30 -2.36; I-2 = 0%) and in the subjects ages 70 and 80 y (OR 1.78, 95% CI 1.51-2.10, I-2 = 71%; and OR 1.96, 95% CI 1.81-2.13, I-2 = 0%, respectively). The quality of associated evidence was low or very low. CONCLUSIONS: Although low-quality evidence was available, we conclude that age is associated with a greater mortality in critical subjects who were receiving mechanical ventilation.
Keywords: elderly; mechanical ventilation; intensive care unit; outcome; age; systematic review